Paradigma Relasi Agama dan Negara dalam Islam - Ridwan Ridwan (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2018)
The paradigmatic debate on the relationship between religion and state in Islam is an actual classic problem. The debate rises due to the absence of the normative basis and historical precedents that definitively state the relation between religion and state. Therefore, the paradigm formulation between religious and state relations is a matter of ijtihadiyah which is always open for debate. This article shows that theoretical debates about the relations between religious and state leads to three paradigms: integralistic, secularistic and symbiotic-mutualistic paradigms.